Flexible Thermoelectric Materials and Generators: Challenges and Innovations - Wang, Yuan; Yang, Lei; Shi, Xiao‐Lei; Shi, Xun; Chen, Lidong; Dargusch, Matthew S.; Zou, Jin; Chen, Zhi‐Gang (Advanced materials (Weinheim), 2019)
The urgent need for ecofriendly, stable, long‐lifetime power sources is driving the booming market for miniaturized and integrated electronics, including wearable and medical implantable devices. Flexible thermoelectric materials and devices are receiving increasing attention, due to their capability to convert heat into electricity directly by conformably attaching them onto heat sources. Polymer‐based flexible thermoelectric materials are particularly fascinating because of their intrinsic flexibility, affordability, and low toxicity. There are other promising alternatives including inorganic‐based flexible thermoelectrics that have high energy‐conversion efficiency, large power output, and stability at relatively high temperature. Herein, the state‐of‐the‐art in the development of flexible thermoelectric materials and devices is summarized, including exploring the fundamentals behind the performance of flexible thermoelectric materials and devices by relating materials chemistry and physics to properties. By taking insights from carrier and phonon transport, the limitations of high‐performance flexible thermoelectric materials and the underlying mechanisms associated with each optimization strategy are highlighted. Finally, the remaining challenges in flexible thermoelectric materials are discussed in conclusion, and suggestions and a framework to guide future development are provided, which may pave the way for a bright future for flexible thermoelectric devices in the energy market. A comprehensive exploration of the material design strategies, processing methods, and underlying physics and chemistry behind the enhanced thermoelectric properties of flexible thermoelectric materials is presented, emphasizing innovative approaches and suggesting future pathways for the development of a new generation of wearable electronics.